Analisis Kesulitan Peserta Didik Pada Pembelajaran Multimedia Materi Desain Grafis Pada Kelas Xi SMKN 2 Kasongan : Analysis of Students' Difficulties in Multimedia Learning Graphic Design Material in Class Xi of SMKN 2 Kasongan - Radityo Surya Ardi Pratama; Chandra Anugrah Putra; Agung Riadin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research aims to determine students' difficulties in learning Multimedia Graphic Design material for class XI at SMKN-2 Kasongan. This research is qualitative research. The data sources for this research are class XI students, class XI teachers and the principal at SMKN-2 Kasongan. The learning studied was Multimedia Graphic Design Material learning. Data collection techniques use observation, interviews and documentation. Three strands of data analysis were used, including data reduction, data presentation and conclusion drawing. Test the validity of the data with serious observation and triangulation of data collection. Based on the research results, it can be concluded that there are several factors that make it difficult for students to learn Multimedia Graphic Design Material for class learning. This results in students not understanding the material presented and finding it difficult to carry out the assignments given. The involvement of a teacher is also important, because if students find it difficult to complete assignments, a teacher can help in completing assignments that students do not understand.